2020
DOI: 10.1002/14651858.cd013459.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests for plague

Abstract: BackgroundPlague is a severe disease associated with high mortality. Late diagnosis leads to advance stage of the disease with worse outcomes and higher risk of spread of the disease. A rapid diagnostic test (RDT) could help in establishing a prompt diagnosis of plague. This would improve patient care and help appropriate public health response. ObjectivesTo determine the diagnostic accuracy of the RDT based on the antigen F1 (F1RDT) for detecting plague in people with suspected disease. Search methodsWe searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In Illustrative examples section, we will demonstrate how the three computational algorithms deal with the data since the existence of such outlying studies may potentially distort the meta-analysis results. Zhao et al BMC Medical Research Methodology (2024) 24:111 In the second example, we present the study by Jullien et al (2020) that studied the diagnosing characteristics of "Rapid diagnostic tests for plague" [16]. As can be seen from the forest plots presented in Fig.…”
Section: Motivating Examplesmentioning
confidence: 98%
See 1 more Smart Citation
“…In Illustrative examples section, we will demonstrate how the three computational algorithms deal with the data since the existence of such outlying studies may potentially distort the meta-analysis results. Zhao et al BMC Medical Research Methodology (2024) 24:111 In the second example, we present the study by Jullien et al (2020) that studied the diagnosing characteristics of "Rapid diagnostic tests for plague" [16]. As can be seen from the forest plots presented in Fig.…”
Section: Motivating Examplesmentioning
confidence: 98%
“…We present the results of fitting the BBN model to the meta-analysis of Jullien et al (2020) [16] in Table 4. The AGHQ algorithm failed to converge with its Hessian matrix being non-positive-definite.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…It is important to note these tests are of differing utility in bubonic and pneumonic plague: the use of a molecular test less specific for pneumonic plague in the 2017 outbreak, which had an unusually high proportion of pneumonic cases, led to initial overestimates of confirmed plague cases before samples were retrospectively tested with a more specific but potentially less sensitive molecular test for pneumonic plague [21]. Notably, the F1 rapid diagnostic test which can be carried out at the bedside, negating some of the geographical issues above, has high sensitivity but does not give the same information on Y. pestis strain or antibiotic resistance as bacterial culture [56].…”
Section: Other Drivers Of Re-emergencementioning
confidence: 99%
“…Previous studies reported that lateral flow assay (LFA) was an ideal platform for diagnosing infectious pathogens (Nardo et al., 2021 ). The test strips currently in use in China mainly adopted paired mAbs against Y. pestis capsule like fraction 1 (F1) protein to detect plague infection (Jullien et al., 2020 ). This antigen has been used for more than a century as a major diagnostic marker and protective antigen (Chanteau et al., 2000 ; Tsui et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%